Akurasi Pemeriksaan Intraoperatif pada Tumor Muskuloskeletal di Instalasi Patologi Anatomi Rumah Sakit Umum Dr. Saiful Anwar Malang periode 2020-2022 - Laitupa, Hamka Muhammad Nasir; Norahmawati, Eviana; Dewi, Rose (Jurnal Klinik dan Riset Kesehatan, 2025)
Background: Frozen section and intraoperative cytology examinations for musculoskeletal tumors are quite necessary, mainly to find out whether a representative specimen can be obtained for a definite diagnosis. Apart from that, it can also be done to determine the radicality of the surgery However, intraoperative pathological examination in musculoskeletal tumours cases as a difficult diagnostic interpretation, one of which may be due to the morphological features of some musculoskeletal tumors are being difficult to differentiate. Aim: To determine the diagnostic accuracy of frozen section and histopathological examination of musculoskeletal tumors. Methods: This study uses a retrospective diagnostic test method which presents the accuracy of frozen section examination compared with histopathological examination as the gold standard in musculoskeletal tumors by determining the sensitivity, specificity, ppv, npv. diagnostic accuracy of musculoskeletal tumors in the Anatomical Pathology Laboratory of Dr. Saiful Anwar Hospital Malang Results: The diagnostic accuracy of frozen section and histopathology examination is 96% with a sensitivity value of 93%, specificity 100%, npp 100%, npn 91.6%. The diagnostic accuracy of imprint cytology and histopathology is 93.7% with a sensitivity value of 93%, specificity 100%, npp 100%, npn 83.3%. The accuracy of intraoperative frozen section and cytology examinations may be influenced by the pathologist's experience, sampling techniques, tissue processing preparations, and the characteristics of the tumor cells themselves. Conclusion: Intraoperative pathological examination can primarily be used to ensure adequate specimens to support the diagnosis of muculoskeletal tumors. Keywords: frozen section; musculoskeletal tumor.